A cross sectional study of elderly widows residing in urban field practice area of S. N. Medical College, Bagalkot, Karnataka - Shankar, Gowri; Ramachandra, Jayaraj M.; Hunshikatti, Sarojini S. (International Journal Of Community Medicine And Public Health, 2018)
Background: Widows are the most vulnerable segment among the elderly population in India. Elderly widows face several social, economic, emotional and cultural deprivations due to their gender, widowhood and old age. Hence, this study was done with the objective to know the socio demographic profile and morbidity of elderly widows residing in urban field practice area of S.N. Medical College, Bagalkot. Methods: This cross sectional study was done in 8 Anganwadi areas during 2016 by cluster random sampling. All the elderly widows residing in the areas were included after informed consent. Ethical clearance was obtained from Institutional review board. Data regarding their socio demographic profile, cause of death of husband, the number of years being a widow, health seeking behavior and their chronic morbidities were noted. Height and weight of each elderly widow was measured and body mass index calculated using the formula weight in kilogram divided by height in meter 2 and classified according to South East Asian category. Blood pressure was recorded three times with the widow in a sitting posture in an interval of 3 minutes and the least value was documented according to JNU classification. Results: Out of 140 elderly widows who were residents of the areas, majority (69.29%) were between 60 to 74 years of age followed by 27.86% between 75 to 89 years of age. It was observed that 75% of them were illiterate. The leading cause of death of husband was coronary heart disease (19.29%), chronic obstructive pulmonary disease (12.86%) and alcoholic cirrhosis (10.71%). On examination of the non-hypertensive widows, it was observed that 36.06% were in Stage I and 22.68% were in Stage II of hypertension (JNU classification). Conclusions: Elderly widows are a vulnerable segment of the community. Their health care needs are a priority and regular health check-ups are to be planned.